ANALISIS PENGARUH LIKUIDITAS SAHAM TERHADAP NILAI PERUSAHAAN MELALUI KEPUTUSAN MANAJEMEN KEUANGAN (STUDI PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA, PERIODE 2016 - 2018) - Margali, Giovanni Edward; Mangantar, Marjam M.; Saerang, Ivonne S. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
LQ 45 is one of the indices on the Indonesia Stock Exchange (IDX), where indexes are obtained by calculating with valuations such as liquidity, in the sense. There are compelling reasons to think that market liquidity will affect company performance. Because of the level of selling power of these shares, it plays a central role in corporate governance, approval and performance. This research itself wants to see the effect of direct liquidity on firm value and the indirect effect of liquidity on firm value by moderating financial management decisions regarding investment decisions, dividend policies and purchasing decisions.In this study,the researchers found that stock liquidity directly affected the value of the company, and stock liquidity did not affect financial management decisions (investment decisions, dividend policies and funding decisions) which would later have an indirect effect on firm value.Keywords : stock liquidity, investment decisions, dividend policy, funding decisions, company value.